Color Removal from Industrial Textile Wastewater Using Chemical Adsorption - Najah M. Al-Shuwaiki; Balasim A. Abid; Mahmood M. Brbooti (Engineering and Technology Journal, 2013)
Industrial wastewaters from local state textile industry (Al-Khadimia Textile Co.) as well as aqueous prepared solutions of color dyes were subjected to simple physico-chemical treatment. The effect of pollutants concentrations, magnesia and other coagulants doses, filtration rate and the overall run time on the water quality were studied in detail. The treatment involves the addition of either magnesia or lime-water suspensions (combined with CPE) in various doses, 0.1-1.0 g/l to the wastewater and colored samples, to study the effect of varying doses on the treatment efficiency. The optimum values of MgO doses were found to be 0.2-0.4 g/l for synthetic colored. Doses of 0.05-0.2 g/l were the best for industrial wastewater. The removal efficiency of all the pollutants in the different samples increases to more than 95% by increasing the pH values to the range of 9.5 to 10 with MgO coagulant and pH of 11.5 to 12 with CaO coagulant. In the jar experiments the rotation speed, N, of 120-140 rpm, for two minutes was the most favorable speed of coagulation mixing for industrial waters. For flocculation, the mixing speed of 35-40 rpm, (G of 40-45 s-1) gave the best removal efficiencies with 20-30 min detention time. At the best operating conditions of the pilot plant, the removal efficiencies of Turbidity, TSS, and color were 97-99%, 94-96%, 94-95%. The TDS removal efficiency was of 39% for Al-Khadimia wastewater.